GC-MS Analysis (Gas Chromatography - Mass Spectrometry) Ethanol Extract (Actinopyga echinites) on The Coast Of Puntondo Beach, District Takalar Ethanol Extract of Actinopyga echinites by GC-MS Analysis (Gas Chromatography - Mass Spectrometry) on The Puntondo Coast, Takalar District - A. Mu’nisa; A. Muflihunna; Hartono (Bionature, 2024)
This research aims to determine the polar bioactive compounds contained in Actinopyga echinites who live on Puntondo Beach, Takalar Regency. Method used for extraction Actinopyga echinitesis a wet maceration method using 96% ethanol solvent. The extract results were analyzed using gas chromatography - mass spectrometry (GC-MS) to obtain information on the internal content Actinopyga echinites. The results of GC-MS analysis from this study showed that there were 123 possible compound components that were extracted using ethanol solvent. Antioxidant capacity was evaluated using the 2,2-diphenyl-β-picrylhydrazine assay. The research results also show that there are ten possible polar bioactive compounds in the highest peak of the GC-MS analysis results, namely: trans-13- Octadecenoic acid, cis-13-Octadecenoic acid, trans-13-Octadecenoic acid, methyl ester, n-Hexane, 9- Octadecenoic acid (Z)-, oxiranylmethyl ester, Hexadecanoic acid, methyl ester, and trans-13-Octadecenoic acid. The presence of estersand dominant fatty acids is thought to cause the high antioxidant activity of antioxidant activity of Actinopyga echinites.